Anti-HBV DNA vaccination does not prevent relapse after discontinuation of analogues in the treatment of chronic hepatitis B: a randomised trial—ANRS HB02 VAC-ADN. Issue 1 (20th February 2014) - Fontaine, H; Kahi, S; Chazallon, C; Bourgine, M; Varaut, A; Buffet, C; Godon, O; Meritet, J F; Saïdi, Y; Michel, M L; Scott-Algara, D; Aboulker, J P; et al.
Abstract : Objective: The antiviral efficacy of nucleos(t)ide analogues whose main limitation is relapse after discontinuation requires long-term therapy. To overcome the risk of relapse and virological breakthrough during long-term therapy, we performed a phase I/II, open, prospective, multicentre trial using a HBV envelope-expressing DNA vaccine. Design: 70 patients treated effectively with nucleos(t)ide analogues for a median of 3 years (HBV DNA <12 IU/mL for at least 12 months) were randomised into two groups: one received five intramuscular injections of vaccine (weeks 0, 8, 16, 40 and 44) and one did not receive the vaccine. Analogues were stopped after an additional 48 weeks of treatment in patients who maintained HBV DNA <12 IU/mL with no clinical progression and monthly HBV DNA for 6 months. The primary endpoint was defined as viral reactivation at week 72 (HBV DNA >120 IU/mL) or impossibility of stopping treatment at week 48. Results: Reactivation occurred in 97% of each group after a median 28 days without liver failure but with an HBV DNA <2000 IU/mL in 33%; 99% of adverse reactions were mild to moderate. Immune responses were evaluated by enzyme-linked immunosorbent spot and proliferation assays: there was no difference in the percentage of patients with interferon-γ secreting cells and a specific T-cell proliferation to HBcAg but not to HBsAg after reactivation in each group. Conclusions: Although it is fairly well tolerated, the HBV DNA vaccine does not decrease the risk of relapse in HBV-treated patients or the rate of virological breakthrough, and does not restore the anti-HBV immune response despite effective viral suppression by analogues. Trial registration number: NCT00536627.